Patient Safety and Quality in Pediatric Hematology/Oncology and Stem Cell Transplantation - Dandoy, Christopher E.; Hilden, Joanne M.; Billett, Amy L.; Mueller, Brigitta U. (Springer International Publishing : Imprint: Springer, 2017)
This volume provides a concise yet comprehensive overview of patient safety issues and quality improvement for the pediatric hematology/oncology/stem cell transplant practice. The book reviews patient safety in complex healthcare delivery systems, delineates the various safety issues affecting pediatric hematology oncology patients, and discusses quality improvement methods and improvement science that allow the reader to implement and sustain change in their home institution. The text also explores mechanisms to measure quality and safety outcomes, allowing the provider to implement proven processes shown to minimize harm to patients. Written by experts in the field, Patient Safety and Quality in Pediatric Hematology/Oncology and Stem Cell Transplantation is a valuable resource for healthcare professionals treating pediatric hematology, oncology and stem cell transplant patients. .
Keywords: Medicine.; Hematology.; Oncology.; elektronické knihy; electronic books